A case of Methicillin-sensitive Staphylococcus aureus infective endocarditis that rapidly changed prognosis in a patient with cirrhosis: An atypical case with literature review. (November 2021) - Sarkar, Taranika; Doshi, Kaushik; Patel, Avani; Mohan, Babu P
Bacterial infections represent a major cause of mortality and morbidity in patients with cirrhosis that can alter the clinical course of compensated cirrhosis. The most common infections are spontaneous bacterial peritonitis by gram-negative organisms, urinary-tract infection, and pneumonia. In this case report, we raise the question of considering infections in the prognosis scoring in this patient group.